2022
DOI: 10.1002/adma.202202942
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Properties of Bi2Te3‐Based Micro–Nano Fibers via Thermal Drawing and Interfacial Engineering

Abstract: High-performance thermoelectric (TE) materials with great flexibility and stability are urgently needed to efficiently convert heat energy into electrical power.Recently, intrinsically crystalline, mechanically stable, and flexible inorganic TE fibers that show TE properties comparable to their bulk counterparts are of interest to researchers. Despite remarkable progress moving TE fibers towards room-temperature TE conversion, the figure-of-merit value (ZT) and bending stability still need enhancement. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
(82 reference statements)
0
18
0
Order By: Relevance
“…The Seebeck coefficients ( S ) or the electrical conductivities ( σ ) of some fibers were measured by the four-probe method [ 20 ]. For each sample, 3-time fiber measurements were carried out under the same conditions, and we used the average values of 3-time fiber measurements as the measuring value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Seebeck coefficients ( S ) or the electrical conductivities ( σ ) of some fibers were measured by the four-probe method [ 20 ]. For each sample, 3-time fiber measurements were carried out under the same conditions, and we used the average values of 3-time fiber measurements as the measuring value.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, researchers have demonstrated ultralong TE fibers by the thermal drawing method to integrate crystalline TE micro/nanofibers into a glass-fiber template [ 15 , 16 , 17 , 18 , 19 ]. Although p-type Bi 2 Te 3 fibers are reported with a high ZT ~1.4 at room temperature [ 20 ], n-type Bi 2 Te 3 fibers have not been systematically studied or improved ZT values effectively by thermal drawing or post-treatment, resulting in TE fiber devices with p-n pairs cannot be widely used. The p-n pair fibers then have the potential to be applied in the field of wearable self-powered devices and temperature-sensing fabrics [ 7 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the ability of crystalline orientation is highly related to the crystal size and orientation degree of the c plane ( F ) [ 6 ]. There have been many studies on the introduction of crystalline orientation at various scales [ 7 , 8 , 9 , 10 , 11 , 12 ]; however, the artificial regulation of crystalline orientation and related mechanisms have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In high-performance thermoelectric fiber devices, p-n Bi 2 Te 3 fibers are usually paired in series electrically and in parallel thermally to realize thermoelectric conversion [ 13 ]. To date, it has been found that the n-type Bi 2 Te 3 fibers (thermally drawn with glass cladding by a powder-in-tube method) could exhibit a restricted ZT < 0.5 owing to the low relative density and more texturing-related sensitivity of the carriers’ mobility than their p-type fibers ( ZT ~1.4) [ 9 ]. In the thermoelectric fibers fabricated by thermal drawing from our previous works [ 14 , 15 , 16 , 17 ], the c -plane crystalline orientation enhances the carrier mobility and electrical conductivity in Bi 2 Te 3 core fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation